Effect of the production of dried fruit and fruit chips on chemical, sensory and bioactive properties - Bahar Kocabıyık; Derya Alkan (Exploration of Foods and Foodomics)
Aim: Dried fruits are consumed by many people around the world as a convenient alternative to fresh fruits with a long shelf life. As well as dried fruits, the manufacturing of baked chips based on fruits having good nutrition and sensory properties represents an alternative to healthier food. The aim of this study is to determine the different chemical properties of dried fruits and fruit chips when they are being fried in ovens. Another aim was to evaluate the changes in total phenolic content (TPC), antioxidant activity, ascorbic acid and hydroxy methyl furfural (HMF) content of chips and dried forms. Methods: In this study, apple, pear, orange, and kiwi were dried in a convection oven at 100°–120°C. Moreover, apple-orange (A-O) and kiwi-pear (K-P) chips were produced in order to develop an alternative product. Dry matter, ash, TPC, ascorbic acid and HMF contents, pH, total acidity and antioxidant activity were determined in fresh, dried and chips samples. Sensory analysis was also carried out in the prepared fruit chips samples using the hedonic scale test. Results: The results revealed that dry matter and ash content increased in dried fruit and fruit chip samples. Drying caused a slight increase in pH and total acidity of all fruit samples. The ascorbic acid contents of kiwi and apple significantly decreased during the drying process. The drying process significantly impacted the total phenol content and antioxidant activity in dried slices. The dramatic increase of HMF was observed during oven-drying and chip production. Conclusions: Based on results, it can be concluded that drying and baking processes had variable effects on the chemical, sensory and bioactive properties of fruit samples. Sensory analysis revealed that A-O chips were more acceptable in terms of sensorial properties compared to K-P chips.